2006
DOI: 10.1007/s00192-005-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum urinary incontinence in a racially diverse obstetrical population

Abstract: To determine the rates of urinary incontinence in a racially diverse, tertiary care obstetrical population during the third trimester and postpartum using a validated symptom-screening questionnaire. Third trimester prenatal patients receiving obstetric care at Loyola University Medical Center between March and November 2003 participated in this prospective study approved by the Institutional Review Board. Third-trimester participants completed the 15-item, validated Medical, Epidemiological, and Social Aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 51 publications
(42 reference statements)
5
36
1
5
Order By: Relevance
“…These results confirmed those obtained in a study conducted in the U.S.A in 2003, which showed no statistically significant difference between continent and incontinent women concerning their mode of delivery (18) . In this regard, this study, showed that UI, in the postpartum, do not depend on the mode of delivery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results confirmed those obtained in a study conducted in the U.S.A in 2003, which showed no statistically significant difference between continent and incontinent women concerning their mode of delivery (18) . In this regard, this study, showed that UI, in the postpartum, do not depend on the mode of delivery.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in agreement with a study done in the U.S.A, in which it was found a prevalence of 46% and 43% respectively (18) , however, it contradicts those other studies conducted in Europe and in Brazil which found higher incidence of UI in multiparous than in primiparous (8,12,19,20) . The analysis of presented studies have shown that parturitions is a determinant risk factor to urinary incontinence in the postpartum.…”
Section: Discussionsupporting
confidence: 86%
“…Studies performed in Denmark and Spain (4,10) found a high association rate between UI in the postpartum and the type of childbirth and with the occurrence of UI during pregnancy. Similarly, a United States study (11) performed with 80 pregnant women with UI found that 44% of the participants continued incontinent after childbirth.…”
Section: Introductionmentioning
confidence: 88%
“…This location was chosen because it offers the chance to be in touch with women who were within six months of the postpartum period. The decision for conducting the interview between 30 days and six months postpartum was based on the fact that literature studies have been performed considering periods within this time interval (10)(11) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation